RAPID URBANIZATION AND HERITAGE CONSERVATION IN INDIAN CITIES - Riganti, Patrizia (BDC. Bollettino Del Centro Calza Bini, 2017)
The paper discusses the issue of heritage conservation in Indian cities in the face of current rapid urbanization trends. The urban development pressure, coupled with the lack of an appropriate conservation framework, is causing the loss of important cultural heritage in India. The federal Indian government has recently launched a program on smart cities to improve cities livability and embrace technological progress. The paper discusses the current policy situation and the role that urban heritage is having within the internal debate. It presents results from an experts’ workshop held in Mumbai in December 2016 and argues that a novel smart heritage approach is needed to support decision making in urban conservation. Keywords: India, smart cities, heritage conservation